Chernets M.V. The influence estimation of radial clearance in sliding bearing on longevity and maximal contact pressures. - Чернець, М.В. (Problems of Tribology, 2014)
The influence of radial clearance magnitude in a sliding bearing with small technological ovality of shaft on its longevity and maximal contact pressures has been investigated. It has been determined, that in the case of radial clearance decrease, the bearing longevity increases and maximal contact pressures decrease both for single-area and double-area contact. In the case of radial clearance decrease in the bearing from 0,41 to 0,11 mm (that is 3,72 times) its longevity increases by 1,84 times. During this process, the starting maximal contact pressures are decreasing for approximately two times and in the result of wear, their further decrease is taking place. When the clearance is approximate to zero ( = 0,01 mm), the longevity increases by 12,1 times. The results of the investigations have been presented graphically and tabularly.